Problems of Mathematics Learning from the Perspective of Senior High School Mathematics Teachers at Limau Bandi School - Zamal, Syahrul; Baiduri, Baiduri; Utomo, Dwi Priyo (Universitas Islam Sultan Agung, 2025)
Mathematics plays a crucial role in various subjects, and educators/students must consider it as an essential element in solving learning problems at the high school level. The purpose of this study is to provide an overview of the problems faced by mathematics learning from the perspective of mathematics teachers. Descriptive qualitative research methods can provide a more comprehensive overview. The researchers then analysed the valid research data using mind mapping through manual data reduction, classification, and coding. The study results indicate that students' focus on memorising formulas rather than understanding concepts causes their difficulty in comprehending mathematical concepts. They also show that negative student motivation and attitudes pose challenging obstacles in teaching mathematics. Additionally, the findings reveal that the limited allocation of learning time is inadequate. The implications are the development of teaching strategies based on conceptual understanding, evaluation of time allocation, and continuous improvement of student motivation in order to change their attitudes to be more positive towards mathematics. Keywords: Conceptual Understanding, Problems of Mathematics Learning, Perspective of Mathematics Teachers.